AMH Concentrations in Peritoneal Fluids of Women With and Without Endometriosis - Kitajima, Michio; Matsumoto, Kanako; Murakami, Naoko; Kajimura, Itsuki; Harada, Ayumi; Kitajima, Yuriko; Masuzaki, Hideaki; Miura, Kiyonori (Frontiers in Surgery, 2020)
[Background] As its name indicates, anti-Müllerian hormone (AMH) is primarily found as an inhibitor of Müllerian duct in male fetus. On the other hand, AMH may act as a mediator of Müllerian duct derived female tissue, such as endometrium in normal and pathological condition. However, the role of AMH in the functional regulations of endometriosis is not well understood. It can be hypothesized that AMH in peritoneal fluids may affect the activity of peritoneal endometriosis. In this study, we investigated the levels of AMH in peritoneal fluids (PF) in women with and without endometriosis. [Methods] PF were collected during laparoscopy from 90 women diagnosed as having advanced endometriosis (rASRM stage III, n=30; stage IV, n=60) and 32 women without endometriosis were served as control. Paired serum samples were also collected before the surgery. AMH in PF and serum were measured by ELISA. Individual clinical information were collected. AMH levels were compared according to the presence of endometriosis. The expression of AMHR2 in peritoneal endometriotic lesions obtained during laparoscopy were examined by immunohistochemistry. [Results] AMH levels in PF were positively and significantly correlated with serum AMH levels in both women with and without endometriosis (R2=0.17, P<0.0001; R2=0.30, P=0.001, respectively). Serum AMH levels were inversely and significantly correlated with age in women with endometriosis (R2=0.092, P=0.004) and in control women without statistical significance (R2=0.078, P=0.12). AMH levels in PF were also inversely but not significantly correlated with age in women with and without endometriosis (R2=0.029, P=0.11 and R2=0.027, P=0.37, respectively). Mean age and serum AMH levels were not significantly different between two groups. On the other hand, AMH levels in PF were significantly lower in women with endometriosis compared to those of control women [2.15±2.13 (mean±SD) vs 4.40±4.77ng/mL, P=0.0001]. AMHR2 are localized at glandular epithelium and stromal cells in ectopic endometrium of peritoneal endometriosis. [Conclusions] Women with endometriosis may present lower PF AMH levels even if they retain serum levels similar to women without disease. As peritoneal endometriosis express specific receptor for AMH, lower AMH levels in PF of women with advanced endometriosis may be involved in the pathophysiology of peritoneal endometriosis.